Dietary nitrate ingested with and without pomegranate supplementation does not improve resistance exercise performance - Tan, Rachel; Price, Katherine M.; Wideen, Lauren E.; Lincoln, Isabella G.; Karl, Sean T.; Seals, Jacob P.; Paniagua, Keonabelle K.; Hagen, Dylan W.; Tchaprazian, Isaac; Bailey, Stephen J.; Pennell, Adam (Frontiers in Nutrition, 2023)
This study tested the hypothesis that co-ingesting nitrate (NO3−)-rich beetroot juice (BR) and pomegranate powder (POM) would enhance neuromuscular performance during vertical countermovement jumps, explosive kneeling countermovement push-ups, and back squats compared to BR ingestion alone. Fifteen recreationally-active males were assigned in a double-blind, randomized, crossover design, to supplement in 3 conditions: (1) NO3−-depleted beetroot juice (PL; 0.10 mmol NO3−) with two empty gelatin capsules; (2) NO3−-rich beetroot juice (BR; 11.8 mmol NO3−) with two empty gelatin capsules, and (3) BR with 1,000 mg of POM powder in two capsules (BR + POM). Participants completed 5 countermovement jumps and 5 kneeling countermovement push-ups interspersed by 1 min of recovery. Subsequently, participants performed 2 sets of 2 × 70% one-repetition maximum back squats, interspersed by 2 min of recovery. Plasma [NO3−] and nitrite ([NO2−]) were elevated following BR and BR + POM compared with PL and POM (p < 0.001) with no differences between BR and BR + POM (p > 0.05) or PL and POM (p > 0.05). Peak power during countermovement jumps increased by 3% following BR compared to BR + POM (88.50 ± 11.46 vs. 85.80 ± 10.14 W/Kg0.67, p = 0.009) but not PL (88.50 ± 11.46 vs. 85.58 ± 10.05 W/Kg0.67, p = 0.07). Neuromuscular performance was not different between conditions during explosive kneeling push-ups and back squats (p > 0.05). These data provide insight into the efficacy of NO3− to modulate explosive resistance exercise performance and indicate that supplementing with BR alone or combined with POM has limited ergogenic potential on resistance exercise. Furthermore, caution is required when combining BR with POM, as this could compromise aspects of resistance exercise performance, at least when compared to BR ingested independently.